The World Bank Group and Public Procurement : An Independent Evaluation - Independent Evaluation Group (Washington, DC: World Bank, 2015)
Good public procurement practices are a major determinant of the effectiveness of public expenditure. Effective policies enable better use of government budgets and are therefore an essential element of the poverty reduction focus of the World Bank. More effective public procurement in countries may also allow procurement practices in the World Bank lending to be unified and harmonized with other donors.